Atlas of virtual colonoscopy comprehensive atlas and fundamentals - Dachman, Abraham H.; Laghi, Andrea; SpringerLink (Online service). (New York Springer, 2011)
Quot;Atlas of Virtual Colonoscopy" thoroughly revises and updates Abraham Dachman's bestselling first edition. Joined in this edition by co-editor Andrea Laghi, Dr. Dachman has expanded the focus of the text to cover fundamental topics of this rapidly evolving technology, including the history of virtual colonoscopy, a review of clinical trial data from throughout the world, and a presentation of clinical background information. Also included are chapters covering patient preparation and tagging, performing and reporting virtual colonoscopy, viewing methods, MR colonography, and computer.
Virtual colonoscopy: from concept to implementation -- Global implementation of computed tomography colonography -- Epidemiology and screening of colorectal cancer -- Implementation and clinical trials in the United States -- Clinical trials in Europe -- Patient preparation and tagging -- Scheduling, performing, and reporting computed tomographic colonography -- Computed tomographic colonography: image display methods -- Nonpolypoid colorectal neoplasia -- Magnetic resonance colonography -- Extracolonic findings -- Computer-aided diagnosis in computed tomography colonography -- Normal anatomy -- Sessile polyps -- Pedunculated polyps -- Diminutive polyps -- Flat lesions -- Stool, diverticulosis -- Masses -- Pitfalls and miscellaneous.
Electronic reproduction.
Keywords: Colonoscopy -- Atlases; Colonoscopy -- Methods -- Atlases; Medicine; Atlases; Electronic books